Religious Choice and Religious Change in Classical and Late Antiquity: Models and Questions - Rives, James (ARYS. Antigüedad: Religiones y Sociedades, 2020)
This paper is an attempt to think broadly about the transformation of religious identity from classical to late antiquity, and the part played in that transformation by conversion.  Beginning with a simple three-point model of religious change, I reconsider A. D. Nock’s classic distinction between conversion and adhesion.  I argue that what really distinguishes classical from late antiquity was not the appearance of religious choices that offered the possibility of a radical reorientation in a person’s understanding of the cosmos, as Nock implies, but rather the development of social structures that transformed that possibility into a necessity, that effectively disallowed adhesion and made conversion the only possible type of religious choice.
Keywords: Religious change; religious identity; conversion; mystery cults; Christianity